Defining Clinical Education: Parallels in Practice - Francina Cantatore; Linda Crane; Deborah Wilmoth (Bond University, 2016)
What is commonly understood by the term 'clinical education'? Despite the attraction of a 'one size fits all' approach, the concept of clinical education is approached differently in diverse disciplines, which may give rise to pedagogical uncertainty. Clinical education in higher education institutions, previously understood to apply exclusively to health professional disciplines, is no longer the sole domain of medicine and health sciences. Instead, it has evolved into an educational model adopted by multiple disciplines to create and implement experiential learning opportunities for students. For example, in the discipline of law it has given rise to law clinics where students are able to deal with real-life clients and obtain professional experience in interviewing and drafting legal letters and documents under close practitioner supervision. In other areas, such as psychology, clinical education has been implemented as an integral part of the educational model through university clinics and external placements that provide the opportunity to practice clinical skills under conditions of supervision prior to becoming registered as an independent practitioner. This paper examines the definition of 'clinical education' in the diverse disciplines of medicine, law and psychology by drawing on available literature and industry practice, and compares and distinguishes the understanding and application of the term in these areas. It further considers whether a cross-disciplinary approach may enhance and inform practices in different disciplines.